Studies on Clinical, Gross, Histopathological and Biochemical Parameters in Broiler Birds Suffered from Eimeria necatrix Infection in Aizawl District of Mizoram, India - Patra, G.; Rajkhowa, T.K.; Ali, M. Ayub; Tiwary, Jully G.; Sailo, Lalhruaitluangi (International Journal of Poultry Science, 2009)
Studies were undertaken to evaluate the clinical, gross, histopathological and some biochemical parameters in broiler birds suffered from E. necatrix infection in a local broiler farm in the Aizawl district. Clinically, 20 birds out of 100 no. (aged between 4-6 weeks) showed loss of appetite, unthriftiness and bloody diarrhoea with mucus. Postmortem examination revealed anaemic pale musculature, distended small intestine with petechial haemorrhages. Similar changes were also observed in some areas of the large intestine and caecum. Histopathological examination showed severe haemorrhagic enteritis with necrosis and disintegration of glandular epithelial cells. Several schizonts were observed in the epithelial cells along with merozoites, infiltrating neutrophils and eosinophils. Biochemically, the infected broilers presented hypoglycaemia associated with a reduction in liver glycogen level. Biochemical serum analysis of coccidia infected chickens also showed a significant increase (p<0.01) in alanine amino transferase levels (2.9-245.2) and there were also changes in total protein and cholesterol level in the serum.